Community Parenting - Laura T. Kessler (Washington University Journal of Law & Policy, 2007)
I have two aims: First, I seek to understand why, at a time of increasing recognition of non-traditional families, the “more-than-two” parent family is so widely agreed to be undesirable, even while so many people practice alternatives to the two-parent nuclear family norm. Second, I seek to move away from derivative, child-focused justifications for expanding the existing legal definition of parent. Instead, I argue for an explicit examination of gender politics. Such an analysis can provide an enriched understanding of functional parenthood. Identity and ideology are already present in contemporary conversations about how best to define parenthood and parental rights. The current singular focus on children’s best interests merely serves to obscure these important subtexts.
Keywords: Unmarried fathers; Surrogate motherhood; Gay couples; Custody of children; Domestic relations law reform; Best interests of the child doctrine; Community parenting; Child custody; Parent and child (Law); United States